The Effectiveness of the Aparatur Sipil Negara Mengajar Program in Fostering English Learning Motivation Among Scavenger Children - Safrina Khaira K; Ema Dauyah; Ferlya Elyza (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study aims to analyze the impact of the Aparatur Sipil Negara Mengajar (ASNM) program on scavenger children’s motivation to learn English at Taman Edukasi Anak Pemulung Gampong Jawa, Banda Aceh. This study employed a qualitative research design. Data were collected through in-depth interviews with three scavenger children from different educational levels and one English teacher involved in the program. The findings reveal that students’ motivation is influenced by both intrinsic and extrinsic factors, including long-term participation (4–6 years), enthusiasm for attending classes, and increased interest in English through creative and interactive teaching methods such as songs and visual media. Teachers play an important role by providing praise, rewards, and positive reinforcement. Supporting factors include patient volunteer teachers, free learning opportunities, and extracurricular activities, while inhibiting factors include fatigue, late attendance, learning difficulties, and peer influence. Overall, the ASNM program successfully fosters a positive learning environment and enhances students’ motivation. The study recommends maintaining varied teaching methods and providing more personalized mentoring to sustain long-term motivation.